(untitled) - McLaughlin, Brett (Beijing, 2002)
"Converting XML documents into Java objects"--Cover; Includes index.
Keywords: Application program interfaces (Computer software); Java (Computer program language); XML (Document markup language); Giao diện chương trình ứng dụng (Phần mềm máy tính); Java (ngôn ngữ lập trình máy tính); XML (Ngôn ngữ đánh dấu văn bản)